2015
DOI: 10.1158/1541-7786.mcr-14-0573
|View full text |Cite
|
Sign up to set email alerts
|

Endophilin A2 Promotes TNBC Cell Invasion and Tumor Metastasis

Abstract: Triple-negative breast cancers (TNBCs) are highly aggressive cancers that lack targeted therapies. However, EGFR is frequently activated in a subset of TNBCs and represents a viable clinical target. Because the endocytic adaptor protein Endophilin A2 (SH3GL1/Endo II) has been implicated in EGFR internalization, we investigated Endo II expression and function in human TNBCs. Endo II expression was high in several TNBC cells compared with normal breast epithelial cells. Stable knockdown (KD) of Endo II was achie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 57 publications
0
29
0
Order By: Relevance
“…It was previously demonstrated that these cholesterol-rich PM microdomains contain MT1-MMP (Annabi et al, 2001;Galvez, 2003). It was proposed that in HT1080 fibrosarcoma cells, MT1-MMP endocytosis is controlled by several clathrin-dependent and -independent endocytic pathways (Baldassarre et al, 2015;Remacle et al, 2003). Although caveolae might interfere with MT1-MMPdependent ECM degradation in MDA-MB-231 cells (Yamaguchi et al, 2009), their direct role in MT1-MMP uptake is unlikely, and they might be involved in membrane and invadopodia organization and in sensing the mechanical stress encountered by tumor cells during invasion (Parton and del Pozo, 2013;Yamaguchi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It was previously demonstrated that these cholesterol-rich PM microdomains contain MT1-MMP (Annabi et al, 2001;Galvez, 2003). It was proposed that in HT1080 fibrosarcoma cells, MT1-MMP endocytosis is controlled by several clathrin-dependent and -independent endocytic pathways (Baldassarre et al, 2015;Remacle et al, 2003). Although caveolae might interfere with MT1-MMPdependent ECM degradation in MDA-MB-231 cells (Yamaguchi et al, 2009), their direct role in MT1-MMP uptake is unlikely, and they might be involved in membrane and invadopodia organization and in sensing the mechanical stress encountered by tumor cells during invasion (Parton and del Pozo, 2013;Yamaguchi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The stable silencing of MMP-14 was carried out using a pLKO.1 lentiviral construct encoding an shRNA targeting human MMP-14 from the TRC library (Dharmacon). Lentiviral production in transfected HEK293 cells, and the transduction and selection of MDA-MB-231 and MDA-Src were performed as previously described [ 34 ]. The extent of MMP-14 KD was evaluated by immunoblot with an MMP-14 antibody (Abcam).…”
Section: Methodsmentioning
confidence: 99%
“…MDA-MB-231 cells were treated with or without Fab 3369 or IgG 3369 at the indicated doses upon seeding on coverslips coated with TRITC-labeled thin gelatin for 18 hours, as previously described [ 34 ]. Degradation spots from epifluorescence micrographs were scored using imaging software (Image ProPlus).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have determined that Endo II plays an important role in cancer biology [ 17 , 21 ]. We have previously reported that Endo II promotes growth, invasion, and metastasis in triple-negative breast cancer (TNBC) models [ 22 ]. There are currently no studies exploring the role of Endo II in HER2+ breast cancer, or its effects on response to treatment with trastuzumab.…”
Section: Introductionmentioning
confidence: 99%